2018
DOI: 10.22216/jk.v3i2.3309
|View full text |Cite
|
Sign up to set email alerts
|

Uji Aktivitas Antijamur Sari Buah Belimbing Wuluh (Averrhoa bilimbi L.) Terhadap Jamur Candida albicans

Abstract: <em>Uji aktivitas antijamur sari buah belimbing wuluh (Averrhoa bilimbi L.) terhadap jamur Candida albicans telah dilakukan dengan menggunakan metode dilusi padat. Penelitian ini bertujuan untuk mengetahui aktivitas antijamur sari buah belimbing wuluh (Averrhoa bilimbi L.) terhadap jamur Candida albicans. Hasil penelitian menunjukkan adanya penurunan  jumlah koloni jamur yang diperoleh pada konsentrasi 100%, 80%, 60%, 40% dan 20% berturut-turut dengan persentase 55%, 48%, 40%, 30% dan 0,16% terhadap pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…bilimbi has also showed efficacy in addressing various health concerns, including asthma, diabetes, cough, fever, and throat soreness (Khoo et al, 2016). In line with previous studies, belimbing wuluh is a promising candidate for use as a functional food raw material due to its rich content of beneficial active compounds, including antioxidants, hypoallergenic, antibacterial, antidiabetic, anti-larvicidal, antifungal, and antiinflammatory components (Octaviani & Fadila, 2018). A comprehensive review study by Lakmal showed that the ethanol extract of its leaves could reduce blood glucose in streptozotocin (STZ)induced diabetic rats at a dose of 125 mg/kg BW.…”
Section: Introductionsupporting
confidence: 53%
“…bilimbi has also showed efficacy in addressing various health concerns, including asthma, diabetes, cough, fever, and throat soreness (Khoo et al, 2016). In line with previous studies, belimbing wuluh is a promising candidate for use as a functional food raw material due to its rich content of beneficial active compounds, including antioxidants, hypoallergenic, antibacterial, antidiabetic, anti-larvicidal, antifungal, and antiinflammatory components (Octaviani & Fadila, 2018). A comprehensive review study by Lakmal showed that the ethanol extract of its leaves could reduce blood glucose in streptozotocin (STZ)induced diabetic rats at a dose of 125 mg/kg BW.…”
Section: Introductionsupporting
confidence: 53%
“…1 mL ekstrak etanol pegagan dilarutkan ke dalam etanol 70% sebanyak 3 ml Ekstrak tersebut kemudian dikocok sembari dipanaskan, lalu disaring. Filtrat yang dihasilkan ditambahkan dengan 0,1 g bubuk magnesium dan beberapa tetes HCl pekat (Octaviani & Fadila, 2018). Kandungan flavonoid ditunjukkan dengan munculnya warna jingga, kuning, dan merah (Aziz, 2015).…”
Section: Uji Fitokimia Flavonoidunclassified
“…Hasil pengujian skrining fitokimia yang telah dilakukan, didapatkan bahwa ekstrak etanol kulit nanas memiliki kandungan senyawa berupa fenolik, flavonoid, steroid, saponin dan alkaloid. Senyawa metabolit sekunder tersebut memiliki aktivitas sebagai antijamur (6,15,16). Senyawa alkaloid bekerja sebagai penghambat biosintesa asam nukleat pada jamur (17).…”
Section: Uji Aktivitas Antijamurunclassified